A consistent view on star-forming galaxies at high redshift from multi-wavelength observations and SED modeling. Issue Volume 11:Issue S319(2015) (17th August 2016) - Schaerer, Daniel; de Barros, Stephane; Boone, Frederic
Abstract: We stress the importance of consistent SED analysis for distant star-forming galaxies (SFGs). We then summarise recent results from such an analysis concerning their basic physical properties, such as the determination of star formation rate (SFR), stellar mass, specific star SFR, UV attenuation, and how this affects our knowledge of star formation properties at high-z.